Beyond soluble transferrin receptor: Old challenges and new horizons. Issue 5 (October 2015) - Harms, Kristian; Kaiser, Thorsten
Abstract : Disturbances of iron metabolism are a frequent challenge in outpatient and inpatient care. Although several established biomarkers are commonly used by clinicians for differential diagnosis, the discrimination between latent or classic iron deficiency, anaemia of chronic disease or a combination of functional iron deficiency (iron-restricted erythropoiesis) with anaemia of chronic disease in patients affected by inflammatory disease can be demanding. Soluble transferrin receptor (sTfR) is a cleaved monomer of transferrin receptor 1 and correlates positively with tissue iron deficiency as well as with stimulated erythropoiesis. The ratio between sTfR and ferritin in combination with reticulocyte haemoglobin content further helps to identify different states of iron deficiency. In this review, we will focus on biological aspects of iron metabolism and sTfR, established clinical applications and limitations of sTfR and derived indices, and prospects of future research and applications.